PHAGO: DIGITAL MEDIA FOR COGNITIVE STRENGTHENING IN THE FIELD OF PHARMACOLOGY - Sunjaya, Vincentius Kevin; Novita Dewi, Bernadette Dian; Wulandari, Yudita (FAKULTAS KEDOKTERAN UNIVERSITAS KATOLIK WIDYA MANDALA SURABAYA, 2024)
Background: In the world of education, studying and learning is required. To keep up with technological advances, learning methods and media are needed that can help students learn. In this research, PHAGO is an interactive learning media which aims to help students understand pharmacology material better and to determine student attitudes and understanding. In this study, the field of urology in geriatrics was chosen because geriatrics is the flagship of FK UKWMS and urology is one of the fields of medicine where geriatric patients often experience disorders.Purpose: To study the influence of geriatric pharmacology digital interactive learning media in the field of urology on the understanding and attitudes of students at the Widya Mandala Faculty of Medicine, Surabaya class of 2020.Method: This research method is pre-experimental research with a One Group PrePost Design research design, namely a research design that provides pre- initial test and questionnaire before administering PHAGO and administering the post-test and final questionnaire after administering PHAGO. The sampling technique in this research is simple random sampling. Sampling was the result of random student pre-tests and post-tests by researchers as well as initial questionnaires and final questionnaires. Statistical analysis for this study used the Wilcoxon Test because the data was not distributed normally.Results: Samples were taken on 21 August 2023 and 11 September 2023 with a total sample of 50 students from the class of 2020 who had never used PHAGO before. The research results obtained are that PHAGO can help students understand pharmacology material and change students’ attitudes from being lazy to being more diligent and an increase in the average value from 25.20 to 55.60 also confirmed the effect of PHAGO on student understanding. Wilcoxon test also gives meaningful results (p = 0.000).Conclusion: It can be concluded that PHAGO has had a good influence on FK UKWMS students’ class of 2020.